Symbolic Representation in the Traditional Ceremony at the Benuaq Dayak of East Kalimantan in Korrie Layun Rampan’s Ceremony Novel - Muhajir, Fatimah M (Jurnal Riseta Soshum, 2024)
Benuaq Dayak is an ethnic group originating from Kutai Kertanegara, East Kalimantan. The uniqueness of the Benuaq Dayak community traditions is represented in a novel entitled Ceremony written by Korrie Layun Rampan. This novel displays the cultural background of the Dayak people in the interior of Kalimantan. It describes a series of ceremonies performed by the Dayak people in their social life. Various traditional ceremonies in this tribe still exist today. This study uses a qualitative descriptive method and uses symbolic theory to examine the meaning of several features of Benuaq Dayak traditional ceremonies. The results of the study show several kinds of symbolic features in ceremonies such as: Balian dance presents symbolic meanings as a form of hope, Kewangkey ceremony represents social esteem. Nalin Taun embodies the purification of the soul and forgiveness of sins, the last one is  Pelulung or marriage ceremony which is followed by a gantar which symbolizes happiness and a symbol of friendship between the two villages.